Service Quality and Trust on Customer Loyalty and Its’ Islamic Perspective of a Package Delivery Services - Syifa Fadhilah, Nur; Kamaruzaman, (Advances in Humanities and Contemporary Studies, 2025)
This study is motivated by the importance of maintaining customer loyalty in the increasingly competitive package delivery service industry, particularly in Sharia-based businesses that emphasize the values of honesty and trustworthiness. The research problem is to determine the effect of service quality and trust on the loyalty of users of the “Kurir Cepat Tanjungpinang” package delivery service in the Riau Islands. This study employs a quantitative method with a survey approach by distributing questionnaires to 75 respondents who are active customers. Data analysis was conducted through validity testing, reliability testing, normality testing, heteroscedasticity testing, multi-collinearity testing, multiple linear regression, as well as t-tests and F-tests. The results show that service quality has a positive and significant effect on customer loyalty. Likewise, customer trust has a positive and significant effect on loyalty. Simultaneously, service quality and trust significantly influence user loyalty. These findings affirm that professional service and maintained integrity can strengthen long-term customer loyalty. In Islamic perspective, the combination of these two represents the implementation of the principles of ihsan (excellence), amanah (trustworthiness), and justice in muamalah (transactions).